VIRTUAL REALITY: A REVIEW OF ITS IMPLEMENTATION IN THE VIRTUAL PHYSICS LAB - A. A. Bakar, N. Azila; Hashim, Shahrum; Shiratuddin, M. Fairuz (Journal of Information and Communication Technology, 2022)
Virtual Reality (VR), being the third era in Human-Computer Interaction (HCI), has opened up opportunities in education. At the same time, VR supports the theory of constructivism. The mode of learning geared towards a student-centric or self directed learning model, is embedded in the constructivism learning philosophy. The VR system is able to display a virtual environment that entirely exists in the computer. It can display three-dimensional (3D) elements of sight, hearing and the sense of touch (haptic). This paper reviews the existing implementation of this promising technology in Physics throughout the world and proposes a solution to tackle the challenges faced by secondary school Physics teachers in Malaysia. The ‘Virtual Physics Lab’ is developed and applied to assist current teaching practices. It is foreseen that when VR is introduced into the Malaysian educational system, the results from this research will be one of the valuable resource to assist the growth of the government’s ‘Smart School’ project. Elementary research methodologies, information gathering, prototype design, development and testing, information analysis and documentation are the steps taken to accomplish the research objectives.